The Analytical Approach to the Competitive Strategy and the Process of its Formation - Časas, Ramunas (Ekonomika, 1999)
This paper aims at taking an analytical look at the concept of competitive strategy taking into account already existing vast theoretical heritage in the strategy research. In particular, this article tries to determine and articulate basic concepts and definitions necessary for the theoretical analysis of competitive strategy and to offer an evaluation of the theories and approaches to the background of formation of competitive strategy. The main sources of information were theoretical works on strategy; strategic management, marketing, articles by researchers and practitioners working in areas related to the aforementioned ones. Reviewing and analysing the contributions of the authors in this field, in the paper the competitive strategy is called “company strategy; seeking competitive advantage”. Although the ability of the company to reach the competitive advantage may be classified as the companyspecific capability; the analysis of various theories has shown that the company can seek the competitive advantage in three distinct ways: by availing itself of unique environmental conditions, by having unique resources or by establishing the relationships and co-operating with other companies. All these concepts are closely linked together and complement each other.